(untitled) (CIPEEX, 2025)
Undergraduate research student (Institutional Scientific Initiation Scholarship Program - PIBIC) affiliated with LAHAC - Cerrado Environmental History Laboratory, acting as an assistant in the doctoral research of the advisor for the project “Trends of Thermal and Environmental Vulnerability in the Goiano Cerrado.” The activities developed included the collection and organization of climate data from NASA (National Aeronautics and Space Administration) and ECMWF (European Centre for Medium‑Range Weather Forecasts). repositories, which were fundamental for building historical series used in the analysis of regional thermal vulnerability. The student also collaborated in the survey and classification of Cerrado phytophysiognomies using the MapBiomas platform, contributing to the characterization of land use and land cover in the study areas. In addition, skills in geoprocessing software were improved, contributing with techniques of spatial analysis and manipulation of meteorological data essential for the development and calibration of the Shannon Index, which assesses the heterogeneity of phytophysiognomies. The research encompassed the integration of different sets of environmental data, microclimate analysis, and the evaluation of the influence of anthropogenic and natural factors on the thermal vulnerability of the Goiano Cerrado. Preliminary results highlight the importance of using remote sensing tools and geotechnologies for understanding environmental risks and supporting sustainable territorial planning. The work also emphasizes the relevance of scientific training in applied research for the development of new researchers in the environmental field.